2020
DOI: 10.1101/2020.07.05.186544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting base editing outcomes with an attention-based deep learning algorithm trained on high-throughput target library screens

Abstract: AbstractBase editors are chimeric ribonucleoprotein complexes consisting of a DNA-targeting CRISPR-Cas module and a single-stranded DNA deaminase. They enable conversion of C•G into T•A base pairs and vice versa on genomic DNA. While base editors have vast potential as genome editing tools for basic research and gene therapy, their application has been hampered by a broad variation in editing efficiencies on different genomic loci. Here we perform an extensive analysis of adeni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…5 for a similar analysis for E. coli datasets. i We applied the same prediction method to a dCas9 dataset from Horlbeck et al 2016 39 and base editing datasets from Marquart et al 2020 40 . Shown are the Pearson correlations between Activity and Predicted Activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 for a similar analysis for E. coli datasets. i We applied the same prediction method to a dCas9 dataset from Horlbeck et al 2016 39 and base editing datasets from Marquart et al 2020 40 . Shown are the Pearson correlations between Activity and Predicted Activity.…”
Section: Discussionmentioning
confidence: 99%
“…While the datasets discussed above are of wild-type Cas9 or Cas9 variants with nuclease activity, we would expect to see similar sequence preference in nuclease null Cas9 variants, including deactivated Cas9 (dCas9) and base editors, if our hypothesis is correct. Using datasets from Horlbeck et al 2016 39 (dCas9) and Marquart et al 2020 40 (base editors) in human cells, we followed the same analysis of the PAM proximal 2 bp sequence that we did for other Cas9 datasets. We found that these datasets shared PAM proximal sequence preference with nuclease active Cas9 datasets in humans but had weaker or negative correlations in other species, despite not inducing double strand breaks (Fig.…”
Section: Pam Proximal 2bp T T a T T C T A A A Cmentioning
confidence: 99%
See 1 more Smart Citation
“…For the normalized absolute number and relative amount of six substitution types, the samples were classified based on the injected chemicals; for each group, the mean and standard deviation were calculated and plotted. To illustrate the potential TadA activity in the samples, the identified TadA motif 39 was used as TadA signature for cosine similarity comparison. The 96-trinuclueotide frequencies were pooled from the two signatures and normalized so that the frequencies add up to 1.…”
Section: Methodsmentioning
confidence: 99%
“…6b,c). In addition, cosine similarity analysis revealed that clones derived from AAV-or LNP-treated mice showed no enrichment in TadA trinucleotide signatures 39 compared to negative control clones (derived from untreated and CBE-treated mice) (Fig. 3c and Supplementary Fig.…”
Section: In Vivo Adenine Base Editing Of Pcsk9 In Macaques Reduces Ldl Cholesterol Levelsmentioning
confidence: 99%